Gender Differences in Work-Family Conflict and Its Impact on Quality of Life: A Qualitative Study in the Healthcare Sector (Journal of Informatics Education and Research, 2025)
This qualitative study investigates gender differences in work-family conflict and their impact on quality of life among healthcare professionals. Using semi-structured interviews and open-ended questionnaires, data were collected from 100 respondents (50 men and 50 women) working in hospitals and clinics. Thematic analysis, supported by SPSS descriptive statistics, revealed that women experience higher levels of work-family conflict, largely due to primary caregiving responsibilities and societal expectations. These conflicts significantly affect women’s mental health and career progression, while men report stress linked to long work hours and evolving family roles. Both genders identified organizational flexibility and spousal support as key coping strategies. The findings highlight the need for gender-sensitive workplace policies, including flexible schedules and equitable parental leave, to mitigate work-family conflict and improve quality of life. This research underscores the importance of addressing gender-specific challenges to support the well-being and retention of healthcare professionals.